Research on the Application of Blockchain Technology in the Optimization of Credit Guarantee and Financing Environment for Small and Medium-sized Enterprises - Fu, Rong (International Theory and Practice in Humanities and Social Sciences, 2025)
Small and medium-sized enterprises, as the indispensable backbone of national economic development, are not optimistic in financing situation due to their narrow direct financing channels and low rate of credit support. At present, due to the characteristics of block chain technology, such as unforgery, traceability, uniqueness and openness, it can bring new development opportunities and change the existing financing mode to a large extent. It can be used to solve some pain points of financing problems of small and medium-sized enterprises and provide new solutions. In this paper, through case analysis of the traditional financing mode of small and medium-sized enterprise financing the main problems and its reason, specify how to combine block chain technology advantage, through the development of chain blocks the technical small and medium-sized enterprise financing difficulties, so as to promote the sustainable and healthy development of national economy, puts forward the construction of credit platform, design the financing mode, optimize the financing environment, such as strategy, It is of great significance to the credit construction and financing development of small and medium-sized enterprises.